Geography and its Role in Sustainable Development and Community Service A Diagnostic Study of the Work Structure of Municipalities in Libya (Journal of Human Sciences, 2021)
This study dealt with geography and its role in sustainable development, community service and a diagnostic study of the work structure of municipalities in Libya. It aimed to identify the role of geography for creating the sustainable development, to identify the areas of work and partnership between service institutions and researchers in the field of geography. It also aimed at identifying the most important modern geographical technologies and techniques and their role in development and to diagnosing the work structure of municipalities in Libya from the perspective of the relationship of geography to development. The importance of this study lies in defining the role of geography in participating in creating the progress that is reflected in community service and in identifying the most important areas of work and partnership with geography departments. This study is also a guiding guide for the competent authorities to define the role and importance of geography, especially the Ministry of Local Government in Libya, which is represented by the municipalities as mini ministries. This is done by relying on secondary sources to collect information, and by the descriptive analytical approach to data analysis. The study reached a set of results and recommendations. The most important results are that geography plays a major role in solving the developmental imbalance problems between the regions. It also concluded that modern geographic techniques increase the value of geographic education because it provides easy entrances to modern information and innovative means of education and teaching. Students who graduate from Geography department have multiple fields to work and partnership other than the field of teaching. It also concluded that the work structure in the municipalities did not give a role and importance to geography in the planning and organization of all community services. Therefore, it emphasized in its recommendations to give a role to specialists in the field of geography to contribute to drawing up spatial development plans, and to focus on the role of modern geographic technologies and software in all stages of education, and not to limit the work fields of geography graduates to teaching only.